Dietética natural: mulheres, ecologismo e espiritualidade na cozinha da Nova Era. - Guedes, Fábio Lúcio Antunes (2015)
Based on ethnographic experience of the encounter from natural and modern kitchens, a therapeutic healing house rises as a representation of a socio-ecological conflict that operates in the formation of different types of cookery expertise. Among 'modern chefs that naturalizes human taste', ‗barefoot female cooks' take us for a walk through the production fields, of commensality of natural foods in search of detailing the historical exclusion of female soul from the art of cookery (DORIA, 2013). Sensitized by a mind-and-body practice based on integrality, openness and attention, this barefoot women seek to grant legitimacy to female devir, in exercising alternative cure methods while facing a quarrelsome modern culinaric habitus responsible for reifying hodiern social gastro-anomie (FISCHLER, 1979). Different theoretical horizons, the dwell perspective (INGOLD, 2011) and acctancy (LATOUR, 1994), were gathered comparatively in order to compose a comprehensive analysis of a ‗eco-vegetarian‘ background, complemented by a parallel ethnographic immersion among producers of organic food in Brazil (ENCA) and Spain (WWOOF) in order to discuss emerging responsibilities in contemporary ecological devir, analysis the anti-ecology immanent in modern dietetic sciences.